Study of biological components of the mine acid drainage generation phenomenology, using the respirometry technique - Martínez Lozano, María del Rocío (2007)
In the present work, the components that participate in the generation of acid mine drainage, in residues that come from the mining industry, were studied, and it was developed in the Faculty of Engenharia do Porto, in Portugal. Geochemical and physical characterization in each of the residuals, in addition to applying static and kinetic methods to evaluate the prediction of acid drainage generation, as an initiative in the research, the respirometry technique was applied, the purpose of which is to quantify the concentration. of oxygen and carbon dioxide that are consumed in the oxidation reaction in wastes that are susceptible to general acid drainage, this evaluation allows us to identify the initial participation of the microorganisms of the genus thiobacillus that participate as catalysts in the reaction.